2019
DOI: 10.1177/2309499019825762
|View full text |Cite
|
Sign up to set email alerts
|

Association between the location of tuberosity cysts and rotator cuff tears: A comparative study using radiograph and MRI

Abstract: Background: The association between tuberosity cysts and rotator cuff tears (RCTs) and the nature of the major contributing factors to tuberosity cyst formation continue to be controversial. The purpose of our study was to evaluate the strength of associations of RCT and various factors involved in the chronicity of RCT with tuberosity cysts, using magnetic resonance imaging (MRI) and radiographs. Methods: We reviewed consecutive patients with various disease entities between August 2004 and July 2013. After e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Degenerative changes on a shoulder radiograph have been shown to indicate fatty infiltration and atrophic changes in rotator cuff muscles. 5 , 13 In the present study, we found that radiographic signs, including GT spur formation, acromial spur formation, and narrow AHI, were associated with the stage of supraspinatus retraction. The combinations of these radiographic signs were highly specific and accurate in terms of predicting advanced retraction of the supraspinatus tendon.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Degenerative changes on a shoulder radiograph have been shown to indicate fatty infiltration and atrophic changes in rotator cuff muscles. 5 , 13 In the present study, we found that radiographic signs, including GT spur formation, acromial spur formation, and narrow AHI, were associated with the stage of supraspinatus retraction. The combinations of these radiographic signs were highly specific and accurate in terms of predicting advanced retraction of the supraspinatus tendon.…”
Section: Discussionsupporting
confidence: 53%
“…Radiographic GT spur and GT sclerosis indicate symptomatic rotator cuff tears 24 and large-sized tears. 18 Cyst formation in the anterior GT 13 and a GT angle greater than 70 degrees 6 have been found to be related to the incidence of rotator cuff tears as well. The combination of these radiographic degenerative signs is effective in ruling out rotator cuff tears when assessed by senior practitioners, 3 with the combined sensitivity and negative predictive value being 91.7% and 80%, respectively.…”
mentioning
confidence: 99%
“…Subcortical cystic changes of the humeral tuberosities (shown in Figures 1-4 ) have an incidence of 15% to 45% in asymptomatic shoulders, with an association with ageing and rotator cuff pathology ( 2 ). They may be further divided based on location, into bare-area, lesser tuberosity, anterior greater tuberosity and posterior greater tuberosity cysts ( 2 , 7 ).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…On MRI, subcortical cysts are seen at the tuberosities and bare area of the humerus as round lesions with low T1 and high T2 signal. These should be differentiated from vascular channels which are connected to tubular structures ( 2 ).…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation